Malnutrition, sarcopenia and current medical use in elderly population - Cebola, Marisa (2019)
Introduction: Ageing leads to an increase in chronic disease’s prevalence, progressive loss of muscle mass, muscle weakness, and polypharmacy, contributing to the establishment of malnutrition and sarcopenia. Objectives: The aim was: 1. Characterize the prevalence of malnutrition, sarcopenia, and current medication use; 2. Relate malnutrition to sarcopenia and current medication use. Materials and methods: Cross-sectional study, developed in the district of Lisbon, in the period from January 1, 2019, to June 30, 2019. Elderly people (≥ 65 years) admitted to the Internal Medicine Unit of a hospital institution (up to 72 hours) were admitted to the study. Participants in this study were the elderly with the capacity to make their informed consent, without the intervention of any element of coercion, with enough knowledge and understanding of the objectives of the study that allowed free and informed decision making. Nutritional assessment was assessed through MNA® and sarcopenia through the SARC-F® Questionnaire. The medication was counted through the number of drugs. Results: n=38 patients, with a mean age of 78.8 + 5.8 years (70-91), born in Lisbon, living in their own home, 50% (n=19) males and 73.6% (n=28) with the first cycle of basic education. At hospital admission 7.9% (n=3) were malnourished, 39.5 (n=15) presented a nutritional risk, 47.4% (n=18) presented a risk of sarcopenia and 60.5% had a prescription of more than three drugs. There was a statistically significant correlation between polypharmacy and malnutrition, (r=0,046). Discussion/Conclusion: The nutritional assessment, presence of sarcopenia and current medication use are extremely relevant at hospital admission. This assessment allows patients to be signaled that they need early nutritional intervention to prevent deteriorating during hospitalization.